2017
DOI: 10.1039/c7ra10869a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gellan and calcium chloride on properties of surimi gel with low and high setting phenomena

Abstract: The properties of bigeye snapper surimi gel as affected by gellan at different levels (2–6% based on solid content of surimi) in combination with CaCl2 at various concentrations (25–75 mmol kg−1) in the presence and absence of transglutaminase were examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…In general, EMC represents the water holding capacity (WHC) of surimi gel. A lower EMC indicates more water retained or bound with the gel matrix [ 13 ]. The EMC of surimi gels containing ASBB at different concentrations is displayed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, EMC represents the water holding capacity (WHC) of surimi gel. A lower EMC indicates more water retained or bound with the gel matrix [ 13 ]. The EMC of surimi gels containing ASBB at different concentrations is displayed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…No differences in the band intensity of actin, tropomyosin, and troponin among all samples were observed between all the gel samples. In general, actin and tropomyosin were not the preferred substrate for TGase and were resistant to proteolysis induced by heat stable proteases [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gelation includes dissociation and unfolding of myofibrillar proteins. A three-dimensional gel network is subsequently developed when unfolded proteins undergo aggregation as induced by heat (Petcharat & Benjakul, 2017). Both dark-and whitefleshed fishes, including fresh water and marine fishes, have commonly been used in surimi production, such as lizardfish (Benjakul, Visessanguan, Tueksuban, & Tanaka, 2004), bigeye snapper (Julavittayanukul, Benjakul, & Visessanguan, 2006), tilapia (Rawdkuen, Sai-Ut, Khamsorn, Chaijan, & Benjakul, 2009), mackerel (Balange & Benjakul, 2009), croaker (Panpipat, Chaijan, & Benjakul, 2010), Alaska pollock (Yin & Park, 2014), silver carp (Majumdar, Deb, Dhar, & Priyadarshini, 2013), and common carp (Ganesh, Dileep, Shamasundar, & Singh, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, COS‐L at high concentration might dilute myofibrillar proteins, thus reducing the aggregation of proteins. This resulted in a less ordered and weaker gel network (Petcharat & Benjakul, ). Amiza & Kang () also reported that gel of surimi from African catfish added with 15 g kg −1 commercial food grade chitosan (MW 10 kDa) had the increase in gel strength by 59%.…”
Section: Resultsmentioning
confidence: 99%